2017
DOI: 10.1371/journal.pone.0171319
|View full text |Cite
|
Sign up to set email alerts
|

Targeted capture enrichment assay for non-invasive prenatal testing of large and small size sub-chromosomal deletions and duplications

Abstract: Noninvasive prenatal testing (NIPT) using whole genome and targeted sequencing has become increasingly accepted for clinical detection of Trisomy 21 and sex chromosome aneuploidies. Few studies have shown that sub-chromosomal deletions or duplications associated with genetic syndromes can also be detected in the fetus noninvasively. There are still limitations on these methodologies such as the detection of variants of unknown clinical significance, high number of false positives, and difficulties to detect sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 55 publications
4
37
1
Order By: Relevance
“…Some previous studies reported that the PPV range of trisomy 21 was 65-94%, trisomy 18 was 47-85%, and trisomy 13 was 12-62% [9][10][11]. There is no difference between this study and the literature reports.…”
Section: Discussioncontrasting
confidence: 64%
“…Some previous studies reported that the PPV range of trisomy 21 was 65-94%, trisomy 18 was 47-85%, and trisomy 13 was 12-62% [9][10][11]. There is no difference between this study and the literature reports.…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, the drawback is that some genes with clinical significance might be hypothetically missed, as some of the deletions have overhangs from the critical regions possibly encompassing genes too. Our study brings also new information that could be used in the further specification of the size as well as localization of the tested microdeletions as both these parameters were found to be between the four most critical ones 6,12 , since there are only very few pathologic detections that overlap the critical regions both from ISCA and DECIPHER databases (Supplementary Table 2).…”
Section: Critical Region Determinationmentioning
confidence: 76%
“…Even though the cost of a screening test is more easily amortized, compared to the cost of treating an affected child [33,34], a lower test cost allows for greater uptake. Our assay's targeted design significantly reduces the number of required reads, resulting in higher efficiency and scalability [7,35]. By combining all these features we can provide a cost-effective, extended carrier screening and NIPT solution to prospective parents, thereby extending the scope of prenatal care.…”
Section: Discussionmentioning
confidence: 99%